2021
DOI: 10.1024/0040-5930/a001274
|View full text |Cite
|
Sign up to set email alerts
|

Post Stroke Depression

Abstract: Zusammenfassung. Die Post Stroke Depression (PSD) ist eine häufig psychische Störung nach einem Insult. Sie beeinflusst den Outcome der Rehabilitation nach Insult und erhöht die Mortalität. Die symptomatologische Beschreibung der depressiven Symptome und Diagnostik erfolgt via ICD-10 Kriterien. Der vorliegende Artikel gibt eine Übersicht über Ätiologische Theorien, diagnostische Ansätze und therapeutische Strategien der PSD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
5
1
Order By: Relevance
“…Research published in Turkey by Karakus et al (2017) mentioned that patients with limited education, who are often the poorest, seem more defenseless than others. However, this contradicts a recent study in the United States that found even higher education levels are vulnerable (Sebestova et al, 2021). The study result for family income is similar to the study discovered in Tanzania by Jones et al (2012), which indicated that lowand middle-income countries suffer more than two-thirds of the global stroke burden, signifying that a clearer understanding of stroke and its wider influence on psychological health makes them less likely to experience health anxiety compared to high-income families from urban areas that are more likely to have health anxiety.…”
Section: The Relationship Between Health Anxiety Score and Socio-demo...contrasting
confidence: 82%
See 1 more Smart Citation
“…Research published in Turkey by Karakus et al (2017) mentioned that patients with limited education, who are often the poorest, seem more defenseless than others. However, this contradicts a recent study in the United States that found even higher education levels are vulnerable (Sebestova et al, 2021). The study result for family income is similar to the study discovered in Tanzania by Jones et al (2012), which indicated that lowand middle-income countries suffer more than two-thirds of the global stroke burden, signifying that a clearer understanding of stroke and its wider influence on psychological health makes them less likely to experience health anxiety compared to high-income families from urban areas that are more likely to have health anxiety.…”
Section: The Relationship Between Health Anxiety Score and Socio-demo...contrasting
confidence: 82%
“…Other than that, the results of this study also found that the level of health anxiety by gender was not significantly associated. In contrast, females have been found to be more prone to experiencing post-stroke anxiety than men, although there is no strong evidence to prove that gender impacts the psychological burden after stroke (Tang et al, 2013;Sebestova et al, 2021). Following that, the marital status of the respondents revealed that there was a significant association between health anxiety and as demonstrated by the recent analyses of Beauchamp et al (2020), it appears that research including more than 200 patients conveys the importance of establishing social support and psychological well-being, which is emphasized by nonmarried status in preventing post-stroke anxiety.…”
Section: The Relationship Between Health Anxiety Score and Socio-demo...mentioning
confidence: 99%
“…Common medications include benzodiazepines, tricyclic antidepressants, SSRIs, and SNRIs ( 3 ). However, the long-term use of antidepressants, potential for dependency, and various side effects have led to an increased focus on non-pharmacological options ( 44 ). These include psychotherapy, cognitive therapy, rTMS, tDCS, electroencephalographic biofeedback therapy, and TCM rehabilitation.…”
Section: Discussionmentioning
confidence: 99%
“…Brain tissue damage occurs in patients after stroke, which may damage the emotional center (14). The reduction of the biochemical transmitter 5-HT and norepinephrine in brain tissues can lead to depression, and the blockade of nerve conduction pathways can also make patients in low spirits (15).…”
Section: Discussionmentioning
confidence: 99%